2002
DOI: 10.1042/cs103s367s
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a selective ETA-receptor antagonist, atrasentan (ABT-627), in murine models of allergic asthma: demonstration of mouse strain specificity

Abstract: Asthma is a chronic respiratory disease that is characterized by airway inflammation, bronchoconstriction and the influx of pro-inflammatory cells, mostly eosinophils in the lung tissue and bronchoalveolar space. Amongst the many physiopathological roles attributed to endothelins (ETs), one is to modulate pulmonary functions. It is established that Balb/c mice develop allergen-induced Th(2)-cytokine gene expression, airway inflammation and hyper-responsiveness whereas C57Bl/6 mice are much less reactive. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…The antagonist of ET A receptor markedly reduced the lung eosinophilia, corroborating previous reports [21][22][23].…”
Section: Discussionsupporting
confidence: 90%
“…The antagonist of ET A receptor markedly reduced the lung eosinophilia, corroborating previous reports [21][22][23].…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, we demonstrated that ET-1-stimulated upregulation of both IL-1β protein production and secretion by HPdLF and KB cells were inhibited by ET A and ET B receptor antagonists, which block the ET-1 signal to the cells. To date, there have been several reports on the inhibition of inflammatory development by ET receptor antagonists in various diseases (15,16,18,28,30). Thus, the inhibition of ET-1 signaling to cells presents a potential therapeutic approach for controlling the IL-1β-dependent inflammatory response, and treatment with an ET A or ET B receptor antagonist may contribute to regulating the inflammation of gingival tissue.…”
Section: Discussionmentioning
confidence: 99%
“…They are 21-residue peptides with 2 intramolecular disulphide bridges. Prominently known for with human psoriasis lesions [67][68][69] [70]) of series designed on a 3,3-diphenyl-2-(pyrimidin-2-yloxy)-propionic acid scaffold [61]. This series has antiinflammatory properties in models of ET-1 induced inflammation and cardiomyopathy and pancreatitis [71,72].…”
Section: Endothelin Receptorsmentioning
confidence: 97%